Designing Carbon Pricing Policies Across the Globe - Frikk Nesje; Robert C. Schmidt; Moritz A. Drupp (CESifo GmbH, 2024)
This study presents a large-scale, global assessment of expert recommendations on key policy design options on how to implement carbon pricing schemes at a country level, for which there is no consensus in the literature. Based on a survey of more than 400 academic experts on carbon pricing, we find that almost twice as many favor a carbon tax over a cap-and-trade scheme for unilateral carbon pricing than vice versa, and three-quarters strongly recommend using border carbon adjustment to address competitiveness concerns. By contrast, guidance on revenue-use from carbon pricing is much more nuanced, with considerably lower support for lump-sum transfers to households than reflected in academic and policy discussions. Furthermore, recommendations on instrument choice and revenue use vary considerably with country- and expert characteristics, such as GDP per capita and academic discipline. Our findings can guide the search for suitable public policy approaches that combine environmental effectiveness with economic efficiency and fairness considerations.
Keywords: Q54; H43; 330; carbon pricing; expert survey; instrument choice; border carbon adjustment; revenue recycling